Cognitive behavior therapy for insomnia in cancer patients: a systematic review and network meta‐analysis. Issue 3 (22nd August 2022) - Gao, Ya; Liu, Ming; Yao, Liang; Yang, Zhirong; Chen, Yamin; Niu, Mingming; Sun, Yue; Chen, Ji; Hou, Liangying; Sun, Feng; Wu, Shanshan; Zhang, Zeqian; et al.
Abstract: Objective: The aim of this study was to examine the most effective delivery format of cognitive behavioral therapy for insomnia (CBT‐I) on insomnia in cancer patients. Methods: We searched five databases up to February 2021 for randomized clinical trials that compared CBT‐I with inactive or active controls for insomnia in cancer patients. Outcomes were insomnia severity, sleep efficiency, sleep onset latency (SOL), wake after sleep onset (WASO), and total sleep time (TST). Pairwise meta‐analyses and frequentist network meta‐analyses with the random‐effects model were applied for data analyses. Results: Sixteen unique trials including 1523 participants met inclusion criteria. Compared with inactive control, CBT‐I could significantly reduce insomnia severity (mean differences [MD] = −4.98 points, 95% confidence interval [CI]: −5.82 to −4.14), SOL (MD = −12.29 min, 95%CI: −16.48 to −8.09), and WASO (MD = −16.58 min, 95%CI: −22.00 to −11.15), while increasing sleep efficiency (MD = 7.62%, 95%CI: 5.82% to 9.41%) at postintervention. Compared with active control, CBT‐I could significantly reduce insomnia severity (MD = −2.75 points, 95%CI: −4.28 to −1.21), SOL (MD = −13.56 min, 95%CI: −18.93 to −8.18), and WASO (MD = −6.99 min, 95%CI: −11.65 to −2.32) at postintervention. These effects diminished in short‐term follow‐up and almost disappeared in long‐term follow‐up. Most of the results were rated as "moderate" to "low" certainty of evidence. Network meta‐analysis showed that group CBT‐I had an increase in sleep efficiency of 10.61%, an increase in TST of 21.98 min, a reduction in SOL of 14.65 min, and a reduction in WASO of 24.30 min, compared with inactive control at postintervention, with effects sustained at short‐term follow‐up. Conclusions: CBT‐I is effective for the management of insomnia in cancer patients postintervention, with diminished effects in short‐term follow‐up. Group CBT‐I is the preferred choice based on postintervention and short‐term effects. The low quality of evidence and limited sample size demonstrate the need for robust evidence from high‐quality, large‐scale trials providing long‐term follow‐up data.